Real-time simulation comparison of the impact of inertia on grid following and grid forming inverter IGBT lifetime - Sunjoh Christian Verbe; Keigo Higashiura; Md. Amit Hasan; Ryuto Shigenobu; Akiko Takahashi; Masakazu Ito; Hisao Taoka (Results in Engineering)
This study examines the thermal effects on Insulated Gate Bipolar Transistors (IGBTs) in Grid-Following (GFL) and Grid-Forming (GFM) inverters under Virtual Synchronous Generator (VSG) inertia control. Using a real-time simulation on a Typhoon Hardware-in-the-Loop (HIL) platform, the research evaluates how varying inertia constants (H = 1, 4, 8 ss) influence IGBT lifespan. Results demonstrate a trade-off between frequency stability and IGBT durability. Higher inertia constants improve grid frequency stability but impose greater thermal stress and power losses, significantly reducing IGBT lifespan. For H = 1, the IGBT lifespan is 174.93 years for GFL inverters and 95.89 years for GFM inverters. At H = 4, the lifespans decrease to 37.05 years and 9.32 years, respectively. For H = 8, lifespans further drop to 9.49 years for GFL and 1.57 years for GFM. These findings highlight the critical balance between maintaining grid stability and ensuring component longevity, offering valuable guidance for optimizing inertia settings in power systems.